BACTERIOLOGICAL EVALUATION AND PHYSICOCHEMICAL COMPLIANCE OF PACKAGED WATER SOLD IN ILORIN, NIGERIA - Jimoh, Fausat Abimbola; Ajao, Abdullahi Taiwo; Aborisade, Wakili Tope; Abdulsalam, Zainab Biola; Kolawole, Matthew Olatunji (FUDMA JOURNAL OF SCIENCES, 2025)
This study evaluated the quality of sachet and bottled water sold in Ilorin, Nigeria. Water samples were procured from selling points, and their physicochemical and bacteriological quality was assessed using standard methods. The results showed that the respective physicochemical parameters for sachet and bottle waters: temperature (26.6 °C and 23.9 °C), electrical conductivity (142.0 µs/cm and 111.0 µs/cm), total dissolved solids (68.5 mg/L and 58.0 mg/L), pH (7.5 and 7.3), and salinity (0.05 and BDL) of both sachet and bottled water samples respectively were within the permissible range recommended by the World Health Organization (WHO). Bacteriological analysis revealed that total heterotrophic bacterial counts (52.5*Z ± 4.7 and 35.0Z ± 0.9) for sachet and bottled water samples were within WHO limits; however, total coliform counts (51.50*Z ± 2.6 and 33.5Z ± 1.5) exceeded the acceptable range of 0 CFU/mL. Seven bacterial isolates identified were Pseudomonas aeruginosa, Klebsiella spp., Proteus spp., Enterobacter spp., Salmonella spp., Shigella spp. and Bacillus subtilis. The number of bacterial isolates in bottled water was higher, with Klebsiella spp. being the most prevalent. The findings suggest varying degrees of microbiological contamination, indicating that some packaged water samples are not of the highest quality. These results highlight the need for stricter monitoring and quality control measures to ensure the safety of packaged water.
Keywords: Packaged water quality; Bacteriological contamination; Physicochemical parameters; Coliform bacteria; Water safety monitoring